Oxidation Artifacts in the Electrospray Mass Spectrometry of Aβ Peptide - Chen, Maolian (2007)
Gradual corrosion of stainless steel electrospray emitters under conditions of normal use generates surface irregularities that can promote electrical discharge. The increased emission current affects the electrochemical reactions associated with the spray process. When sampling the peptide Aβ(1–40), this is manifest by oxidation of methionine at position 35 to methionine sulfoxide. The resultant mass shift and reduced sensitivity can adversely affect H/D exchange experiments. These effects can be avoided by adding a redox buffer or (preferably) by re-polishing the emitter, especially to a rounded geometry.